PENGEMBANGAN MEDIA PEMBELAJARAN ADOBE FLASH CS5 PADA PEMBELAJARAN MENULIS TEKS EKSPLANASI KELAS XI SMA NEGERI 1 PADANG BOLAK - Riky Gunawan Siregar (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2019)
PENGEMBANGAN MEDIA PEMBELAJARAN ADOBE FLASH CS5 PADA PEMBELAJARAN MENULIS TEKS EKSPLANASI KELAS XI SMA NEGERI 1 PADANG BOLAK  Riky Gunawan Siregar Program Studi Magsiter Pendidikan Bahasa dan Sastra Indonesia Universitas Negeri Medan Email: rikygunawansiregarpahu@gmail.com  Abstract This study aims to determine the results of the development of Adobe Flash CS5 Learning Media on Learning Text Writing Explanations. This type of research is development research based on the 4-D development model. This research was formed from design experts, material experts, Indonesian language teachers, and XI grade students of SMA Negeri 1 Padang Bolak. The results showed that (1) the validation of the material experts included the content worthiness of 86.5% in the good category, the feasibility of serving Adobe Flash CS5 88.5% in the good category, the aspect of Adobe Flash CS5 87.5% in the good category, the aspect of language assessment 90% excellent category, (2) design expert validation includes initial design 85.7% with good category, content design 82.1% good category, adobe flash CS5 typography 79.1% good category, and content illustration 79.1% good category . (3) limited trials get a score of 81.4% with good criteria (4) Expanded trials get a score of 80.4% in the good category. Learning outcomes producing explanatory text before using Adobe Flash CS5 gained 68.7 while learning outcomes producing Adobe Flash CS5 text using Adobe Flash CS5 gained 81. The difference gained 12 from before and after using Adobe Flash CS5. This research has implications that Adobe Flash CS5 developed will provide practical contributions, especially in the implementation of the learning process for teachers as additional learning media to provide facilities for the material being taught can be independent or classical. Furthermore, students can improve the quality of learning, especially in explanatory text writing activities.Keywords: Adobe Flash CS5, Explanatory Text.